PENYUSUNAN DAN VALIDASI MODEL ALOMETRIK BIOMASSA POHON EUKALIPTUS HIBRIDA DI UNIT PENGELOLAAN HUTAN TANAMAN DI SUMATRA UTARA (Jurnal ForestrIndo, 2024)
Information on tree biomass potential is closely related to the ability of vegetation to absorb CO2, which is one of the pollutants that can cause the greenhouse effect. Eucalyptus is one of the tree species cultivated in industrial plantation forests in Indonesia, with a relatively short rotation period (3–5 years), and can act as a carbon dioxide absorber. This study aims to develop an allometric model to estimate the total biomass of hybrid eucalyptus trees in a plantation forest management unit in North Sumatra. The sample trees used in this study included 75 trees with diameters ranging from 1.46 to 17.52 cm. The allometric models were developed using CurveExpert Basic 2.2.3 and RStudio 4.4.0, resulting in five selected models: power (M1), exponential (M2), polynomial (M3), rational (M4), and Hoerl (M5). Subsequently, these five models were validated, also involving two others previously existing allometric models at the same site, ultimately resulting in model M1 (W = 0.08378D^2.49572) as the best model. This model, based on this study, demonstrated better accuracy compared to other allometric models for estimating the biomass of hybrid eucalyptus trees at the study site.